Should the rich be taxed more? The fiscal inequality coefficient - John Hatgioannides; Marika Karanassou; Hector Sala (Queen Mary University of London, School of Economics and Finance, 2017)
This paper holistically addresses the effective (relative) income tax contribution of a given income (or, wealth) group. The widely acclaimed standard in public policy is the absolute benefaction of a given income group in filling up the fiscal coffers. Instead, we focus on the ratio of the average income taxrate of an income group divided by the percentage of national income (or wealth) appropriated by the same income group. In turn, we develop the Fiscal Inequality Coefficient which compares the effective percentage income tax payments of pairs of income (or wealth) groups. Using data for the US, we concentrate on pairs such as the Bottom 90% versus Top 10%, Bottom 99% versus Top 1% and Bottom 99.9% versus Top 0.1%. We conclude that policy makers with a strong social conscience should re-evaluate the progressivity of the income tax system and make the richest echelons of the income and wealth distributions pay a fairer and higher tax.
Keywords: H23; H30; E64; 330; Fiscal policy; progressive income taxation; inequality; effective income tax rate; fiscal inequality coefficient